Women’s Economic Empowerment through Microfinance: Insights from the Urban Poor in Kathmandu - Shrestha, Niyam Raj (PYC Nepal Journal of Management, 2024)
Microfinance has become a pivotal mechanism for poverty alleviation and financial inclusion, particularly in developing countries like Nepal. This study explores the role of microfinance institutions (MFIs) in promoting socio-economic empowerment, with a specific focus on urban poverty and women's participation. This research is conducted with primary survey data and employs a quasi-experimental design to compare participants and non-participants in a Lumanti-supported microfinance initiative. Findings indicate significant improvements in participants' income levels, household assets, education, healthcare access, and decision-making capacity. The study's regression model confirms that microcredit participation, along with factors such as business size and family income, has a positive influence on household income. Participants reported high satisfaction with credit services, particularly compared to traditional banks. Despite challenges such as irregular incomes and operational inefficiencies, the results support microfinance as a powerful tool for empowering women and reducing urban poverty. The study recommends adopting client-centric, sustainable microfinance models to amplify social and economic outcomes in urban poor settings.